Brucellosis and its effect on animal production In Iraq (Eurasian Medical Research Periodical, 2022)
This article highlight on the Brucellosis and its effect on animal production In Iraq. Brucellosis  is a common zoonotic disease, which may spread widely in Iraq and neighboring countries, with great economic loss for livestock and their products. This study aims to identify the main features of brucellosis and virulence factors present in animals infected with brucellosis, as well as study the prevention and treatment of brucellosis. Brucellosis is an occupational disease that mostly affects those who work with infect animal or their tissue, particularly farm employees, veterinarians, slaughterhouse workers, and microbiology laboratory workers. Brucella penetrates macrophages and contains lipopolysaccharides, which are the main virulence factors. Here the bacteria multiply and arise intracellularly in the host resulting in immunosuppression and chronic infection.  Brucellosis in Iraq was motionless an widespread and dangerous disease amongst domestic animals and humans, despite the attempt that have been implement in the country to control the disease, whether through bilateral projects with some parties or international organizations. The conclusion showed  Brucellosis was an infectious disease causing disease in humans and domestic animals, and able to exist in both( intracellular and extracellular) environments. Avoidance of human brucellosis relies mainly on control the infection in animals